Association of nonmodifiable risk factors with Alzheimer disease blood biomarkers in community-dwelling adults in the ESTHER study - Stocker, Hannah; Beyer, Léon; Trares, Kira; Stevenson-Hoare, Joshua; Rujescu, Dan; Holleczek, Bernd; Beyreuther, Konrad; Schöttker, Ben; Gerwert, Klaus; Brenner, Hermann (Neurology, 2025)
Background and Objectives: Dementia-related blood biomarkers are the future of large-scale dementia risk stratification; however, the extent to which phosphorylated tau (P-tau181), neurofilament light (NfL), and glial fibrillary acidic protein (GFAP) are associated with nonmodifiable risk factors has yet to be confirmed in the community, and the role of menopause has yet to be investigated. Therefore, the aim of this study was to examine the association of age, sex, APOEe4 status, and menopause, with dementia-related blood biomarker levels (P-tau181, NfL, and GFAP) and rate of change over 11 years in longitudinal biomarker measurements in community-dwelling adults. Methods: Within this German population-based Epidemiologische Studie zu Chancen der Verhütung, Früherkennung und optimierten Therapie chronischer Erkrankungen in der älteren Bevölkerung cohort study (n = 9,940), a nested case-control study of 1,026 participants (1:1, without dementia during follow-up: incident dementia during follow-up) aged 50–75 years at baseline followed over 17 years was conducted. Blood biomarker measurements (P-tau181, NfL, and GFAP) were completed in blood from baseline, 8-year, and 11-year follow-ups, and cross-sectional and longitudinal regression analyses were used to assess the association with age, sex, APOEe4, and menopause. Results: The mean age of participants was 64 years, and women accounted for slightly over half (54%) of the sample. Age was cross-sectionally and longitudinally significantly associated with all dementia-related biomarkers (p < 0.001). NfL and GFAP levels more strongly correlated (Spearman R = 0.55 and 0.49) with age at baseline than P-tau181 levels (Spearman R = 0.21). Women experienced significantly higher levels and rates of increase in GFAP (p < 0.001) while men experienced higher levels of NfL after adjusting for age and APOEe4 (p < 0.01). APOEe4 status was significantly associated with baseline and longitudinal levels of P-tau181 (baseline β = 0.30, p < 0.05) and GFAP (baseline β = 15.84, p < 0.001). Of interest, premenopausal status was significantly associated with higher GFAP levels after adjusting for age, sex, and APOEe4 (β = 19.09, p < 0.05). Discussion: This population-based study on dementia biomarkers found that P-tau181 was dependent on age and APOEe4; NfL on age and sex; and GFAP on age, sex, APOEe4, and menopause status. GFAP levels and rate of increase were higher in women, especially in premenopausal participants. Future research should confirm these findings and further explore the role of menopause in dementia pathogenesis among women.
Online veröffentlicht: 16. April 2025
Gesehen am 01.10.2025